Improving Access to Financial Services in Poor Communities: Introducing the Graduation Microfinance Model in The Gambia, 2015–2018 - Yankuba K., Touray (KDI School of Public Policy and Managment, 2019)
Across The Gambia, many people lack access to basic financial services that would allow them to borrow and save money. The problem is particularly prevalent in rural areas, where very few banks have branches, and as a result, most rural dwellers—particularly women—remain unbanked. Without savings or access to credit, families struggle to grow their income and improve their wellbeing. To address the problem, Irish Aid, Ireland’s international development aid organization, funded Improving Access to Pro-Poor Financial Services in Sierra Leone and The Gambia, a project launched in 2015 by the National Association of Cooperative Credit Unions of The Gambia (NACCUG) (Dalzell and O’Sullivan 2018). The initiative aimed to provide financial services to poor rural communities by helping credit unions—membership-based financial cooperatives—to implement “graduation microfinance,” a loan system for groups of people who do not individually qualify for credit union membership. After paying back a loan as a group, each group member would became eligible to join the credit union as a full member. However, NACCUG first had to convince the credit unions to make group loans in the targeted communities as well as find a way to teach financial management skills to people with little or no formal education. The project facilitated the creation of 39 graduation microfinance groups with more than 600 active saving members and 300 borrowers. By May 2018, 93 individuals had graduated to full credit union membership. The project helped create a culture of saving in the targeted areas in rural parts of The Gambia and helped women in those communities improve how they managed their finances. The 600-plus active saving members who participated in the project can now access loans to invest in their businesses and can use the profits to pay for household expenses and their children’s education.